2014
DOI: 10.1242/jcs.140426
|View full text |Cite
|
Sign up to set email alerts
|

The LC3 interactome at a glance

Abstract: Continuous synthesis of all cellular components requires their constant turnover in order for a cell to achieve homeostasis. To this end, eukaryotic cells are endowed with two degradation pathways -the ubiquitinproteasome system and the lysosomal pathway. The latter pathway is partly fed by autophagy, which targets intracellular material in distinct vesicles, termed autophagosomes, to the lysosome. Central to this pathway is a set of key autophagy proteins, including the ubiquitin-like modifier Atg8, that orch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
243
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(246 citation statements)
references
References 125 publications
(75 reference statements)
2
243
0
1
Order By: Relevance
“…4A, B and D). Given the large number of LIR-containing proteins in mammalian genomes, 24,25 it is likely that other LIR motifs may also interact with Atg8-family proteins using a similar binding mode that we have discovered for FYCO1 LIR. Indeed, further sequence analysis of the currently known 43 In this presentation, the LC3A molecule is shown in the surface model and FYCO1 LIR in the ribbon-stick model.…”
Section: Detailed Comparisons Of the Fyco1 Lir-binding Mode With Currmentioning
confidence: 60%
See 1 more Smart Citation
“…4A, B and D). Given the large number of LIR-containing proteins in mammalian genomes, 24,25 it is likely that other LIR motifs may also interact with Atg8-family proteins using a similar binding mode that we have discovered for FYCO1 LIR. Indeed, further sequence analysis of the currently known 43 In this presentation, the LC3A molecule is shown in the surface model and FYCO1 LIR in the ribbon-stick model.…”
Section: Detailed Comparisons Of the Fyco1 Lir-binding Mode With Currmentioning
confidence: 60%
“…Accumulating evidence showed that the specific interactions between Atg8-binding proteins and Atg8-family proteins were mainly mediated by a short motif named LC3-interacting region (LIR). [20][21][22][23][24][25][26][27][28][29] The canonical LIR motif has the consensus core sequence QxxG where Q being aromatic residues (W/F/Y), and G being bulk hydrophobic residues (L/I/ V). 17,26 Additional acidic residues and/or serine/threonine phosphorylation sites preceding the hydrophobic LIR core sequence are also commonly found in LIR-containing proteins, and are demonstrated to regulate their specific interactions with Atg8-family members.…”
Section: Introductionmentioning
confidence: 99%
“…One important function of LC3 is recruiting autophagic proteins to autophagosomes for assembly of functional autophagosomal complexes by interacting with the LIR (LC3-interacting region) domain-containing proteins. 18,19 Currently, more than 100 proteins have been identified containing the LIR domain. 19 One relevant example is the core autophagic protein SQSTM1/p62.…”
Section: Introductionmentioning
confidence: 99%
“…LC3-Ⅱ is employed to the membrane of the autophagosome and specifically mediates elongation of the autophagosome. Therefore, the ratio of LC3-Ⅱ to LC3-Ⅰ will become larger when the quantity of autophagosomes increases (7). In addition to the shift of LC3-Ⅰ to LC3-Ⅱ, another crucial ATG protein P62 that interacts with ubiquitinated proteins through its UBA domain (ubiquitin-associated domain) and then delivers them to LC3-Ⅱ via another domain LIR (LC3-interacting region) will be finally degraded in the autolysosome, so the level of P62 has a contrary relationship with autophagic activity (8).…”
Section: Introductionmentioning
confidence: 99%